Technical Note: Patterns of Urban Forest Debris from the 2004 and 2005 Florida Hurricane Seasons (2009)
Urban tree debris generation and damage resulting from seven hurricanes during the 2004 and 2005 Florida hurricane seasons was analyzed using a random sample of communities in highly affected counties. Woody debris amounts, rates, and costs for cleanup were quantified, as were the spatial patterns of damage across the state. Average debris volume per mile of street segment was 488 cubic yards, and cost of removal and disposal averaged $21.50 per cubic yard. Urban forest structure, community characteristics, and hurricane severity influenced debris and cost results. Spatial analyses indicated that debris results were clustered into northwest and southeast areas of the state, which represent two distinct ecoregions in Florida. Although southeastern Florida had much higher costs per cubic yard than the northwest, the debris volume per road mile was higher in the northwest portion of the state. On a per-mile basis, Hurricane Ivan was responsible for the greatest debris volume, and Hurricane Katrina was the most expensive. These results can be used to help communities plan for hurricane response and management activities and to estimate potential damage to their urban forest resource.